Evaluation of mPEG effect on the hydrophilicity and antifouling nature of the PVDF-co-HFP flat sheet polymeric membranes for humic acid removal. (December 2016) - Singh, Randeep; Purkait, Mihir Kumar
Highlights: mPEG modified PVDF-co-HFP membranes were fabricated by using NIPS technique. Effect of mPEG on the membranes morphology and permeation properties was studied. Antifouling properties of the membranes were tested with BSA and HA solutions. The antifouling nature and hydrophilicity of the membranes were increased with increased mol wt. of mPEG. The membranes have shown a better rejection profile for BSA and HA rejection. Abstract: In this study PVDF-co-HFP flat sheet membranes were prepared by using methoxy poly(ethylene glycol) (mPEG) of three different molecular weights (550 Da, 2000 Da and 5000 Da) to improve hydrophilicity and antifouling characteristics of the membranes. mPEG of different molecular weights were added with Poly(vinylidene fluoride- co -hexafluoropropylene) (PVDF-HFP) in N-methyl-2-pyrrolidone (NMP) to prepare the membranes by using non solvent induced phase separation (NIPS) technique. The improvements in the membrane attributes were studied under two categories viz. morphological and permeation. Field emission scanning electron microscopy (FESEM) and atomic force microscopy (AFM) were used to study the morphological properties of the prepared membranes. Presence and stability of the additive (mPEG) in the prepared membranes were confirmed by using the Fourier transform infrared spectroscopy (FTIR). Permeation studies of the prepared membranes were done in the form of pure water flux (PWF) and hydraulic permeability. Equilibrium water content (EWC) and water contact angle of the prepared membranes were calculated to analyze the increase in hydrophilicity of the prepared membranes. Antifouling studies on the prepared membranes were done by using bovine serum albumin (BSA) and humic acid (HA). The modified PVDF-co-HFP membranes have shown a 50% increase in the PWF with an increase in the molecular weight of mPEG from 550 Da to 5000 Da. The increase in hydrophilicity and antifouling nature leads to an increased EWC, from 36.17 to 62.62. The water contact angle also decreases from 71.32° to 59.45° with an increase in the molecular weight of mPEG. Antifouling study with BSA and HA further confirms the increased antifouling nature of the prepared membranes, due to the presence of mPEG in the membranes. The proof of the same is presented in the form of flux recovery ratio, which increases from 73.07 to 87.47. The prepared membranes have shown good rejection profiles for both BSA and HA at 95% and 99%, respectively.